(3TQM MeGSI CHj JeGes - (3CHi MLGL jhSa Hf SdeGf Hf YjSis; (3CHh JeGe GdWGFj , CHh JeGe MHjH Hf ChS Hf GdMGQK GdWGFj,J (B231 (3g` s
(3ChdgG (B:s
(3HGH GdMeGSI, hgj GdTLGYI bGajg GdCda bGd bjS Hf GdNWje(B: (3KGQJ YQjG hGdNWje ade CUZ hLHg CTjGN LYdJ ERGAgG s
(3BNQgG (B:s
(3aCHYOg GdEdg hdG jMji hdG jTai ef GdeQV GdTfGjG Je hGdMeO ddg hMOg s
(3GdfSNI HgG MhGTs
(3JQJjH GdCYde GdTfJeQi GdfSNI NGdjg ef ebOeI GdTGQM hNGJeJgs
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdCOHs